HUBUNGAN ANTARA PEMAKAIAN SEPATU HAK TINGGI DENGAN TERJADINYA PATELLOFEMORAL PAIN SYNDROME DAN PERUBAHAN SUDUT QUADRICEPS PADA SALES PROMOTION GIRL DI MATAHARI KOTA JAMBI - Putra Hadi (Jurnal Akademika Baiturrahim Jambi, 2017)
Background: The incidence of patellofemoral pain syndrome quadriceps angle of sales promotion girl can caused be standing static position for a long time. Pain is experienced will cause changes in the position of the pedestal to the knee that causes changes in the quadriceps angle. Methods: The survey method of Analytical observation with cross  sectional. The design of this research is Point Time Approach, observation subject is only once and the measurements made of the status a character or a variable subject on the inspection, to take a sample with a total sampling method. The normality Test with kolmogrov-smirnov, bivariate relationships with the chi square test. Subjek numbered at 30 people.Results: The results of the relationship test is p-value <0.05 in patellofemoral pain syndrome and quadriceps angle changes.  There is a significant relationship to the occurrence high heels usage Heigh patellofemoral pain syndrome and quadriceps angle changes.